Female rugby union injuries in New Zealand: A review of five years (2013–2017) of Accident Compensation Corporation moderate to severe claims and costs. Issue 5 (May 2019) - King, D.; Hume, P.A; Hardaker, N.; Cummins, C.; Clark, T.; Pearce, A.J.; Gissane, C.
Abstract: Objectives: To provide epidemiological data and related costs for moderate-to-serious and serious injury claims for women's rugby union in New Zealand. Design: A retrospective analytical review of injury entitlement claims for women's rugby from 2013 to 2017. Methods: Data were analysed by year of competition, age, body site and injury type for total and moderate-to-severe (MSC) Accident Compensation Corporation (ACC) claims and costs. Results: Over 2013 to 2017 there were 26, 070 total claims for female rugby union costing $18, 440, 812 [AD$16, 956, 998]. The 15–19-year age group recorded 40% (n = 1, 009) of the total female rugby union Moderate-to-serious and serious (MSC) claims and 41% ($5, 419, 157 [AD$4, 983, 112]) of the total female rugby union MSC costs. The knee was the most commonly recorded injury site accounting for 40.3% (n = 1, 007) of MSC claims and 46.9% ($6, 229, 714 [AD$5, 728732]) of MSC costs with an average cost of $1, 245, 943 ±$217, 796 [AD$595, 351 ±AD$104, 070] per-year for female rugby union. Conclusions: This is the first study to report the nature and related costs for moderate-to-serious and serious injury claims for women's rugby union in New Zealand. A total of 26, 070 injury claims were lodged over the duration of the study but only 9.6% (n = 2, 501) of these were classified as MSC injury entitlement claims. Participants 25 years and older accounted for 31% of the female rugby union player claims. Females in the over 35-year age groups compete against younger participants which may account for the higher mean cost per-claim seen as the age groups increase in years until they retire from the game.